Japan's quest for stability in Southeast Asia navigating the turning points in postwar Asia - Miyagi, Taiz?o 1968- (Routledge contemporary Japan series)
More than any other region in the world, Asia has witnessed tremendous change in the post-war era. A continent once engulfed by independence and revolution, and later by the Cold War and civil war, has now been transformed into the world's most economically dynamic region. what caused this change in Asia? The key to answering this question lies in the post-war history of maritime Asia and, in particular, the path taken by the maritime nation of Japan. Analyzing the importance of Japan's relationship with Southeast Asia, this book aims to illustrate the hidden trail left by Japan during the period of upheaval that has shaped Asia today - an era marked by the American Cold War strategy, the dissolution of the British Empire in Asia, and the rise of China. It provides a comprehensive account of post-war maritime Asia, making use of internationally sourced primary materials as well as declassified Japanese government papers. As such, this volume will be useful to students and scholars of Japanese politics, Asian politics, and Asian history.